Initially Synthesize [BMIM]CL and Apply to Extract Cellulose from Banana Rachis - Tran, An T.T.; Vo, Huy T.; Nguyen, Quan D. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2017)
Ionic liquors are organic salts with cations as organic and anionic inorganic bases, which exist in a viscous liquid state than organic solvents. The banana rachis is one of the agricultural products from banana trees. In Vietnam, bananas are high yield fruit trees. The amount of debris from banana trees is quite large but not yet utilized effectively to bring economic value. Banana rachis material is utilized and treated with 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) ionic liquid to initially investigate the ability of cellulose to separate the ionic liquid from the banana rachis. Banana rachis processing by [BMIM]Cl was investigated at 80oC, 100oC, 120oC and 140oC for 1 hour. Then analyze the reducing sugar and cellulose ingredients in the banana rachis samples. The results showed that the optimum temperature for banana rachis processing with [BMIM]Cl is 140°C for 1 hour. Ionic liquid in general and [BMIM]Cl in particular have great potential in the processing of fruit waste. Specifically, the content of cellulose in the banana kernel after treatment [BMIM]Cl was 73.04±7.49% compared to untreated sample was 26.25±1.43%, 3 times higher . The results of FTIR of banana rachis and recycled [BMIM]Cl showed that the lignin component in the banana rachis was quite soluble, resulting in a significant increase in cellulose content.